2011
DOI: 10.1021/jp109853f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Soot Nanoparticle Inception via Polycyclic Aromatic Hydrocarbon Coagulation (Condensation): Energetic, Structural, and Electronic Features

Abstract: Carbon nanoparticles, generated during combustion at relatively low [O 2 ], or under pyrolysis conditions, can be seen both as soot precursors and as primary pollutants in themselves, since they are also directly emitted in the troposphere by vehicles. Soot particle inception (transition of relatively low-mass molecular systems from the gaseous phase to a solid nature) occurs at least in part via polycyclic aromatic hydrocarbon (PAH) coagulation/condensation. Complexes of different PAH systems, bound only by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 70 publications
(78 reference statements)
2
13
0
Order By: Relevance
“…However this result has been challenged both by further modeling studies [5][6][7] and experimental results [8]. This has motivated many modeling studies in which the clusterization of PAH-like species has been evaluated as a function of different parameters such as PAH size or the presence of aliphatic chains but also by considering chemical dimerization as a way to increase the stability of these species at high temperature [9][10][11][12][13][14][15][16][17]. Soot nucleation might therefore be induced by three-dimensional crosslinked structures rather than by stack clusters [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…However this result has been challenged both by further modeling studies [5][6][7] and experimental results [8]. This has motivated many modeling studies in which the clusterization of PAH-like species has been evaluated as a function of different parameters such as PAH size or the presence of aliphatic chains but also by considering chemical dimerization as a way to increase the stability of these species at high temperature [9][10][11][12][13][14][15][16][17]. Soot nucleation might therefore be induced by three-dimensional crosslinked structures rather than by stack clusters [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1016/j.combustflame.2013.11.023 particles of nanometric size. There is general agreement that aggregation of PAH molecules is a likely first step of soot particle nucleation [2][3][4][5][6][7]. Therefore, accurate knowledge of the kinetics of one and two ring aromatic chemistry predating PAH formation is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure a exemplifies a complex, shown only for system 1 (those for the other systems are similar). The parallel arrangement of the two moieties reflects vdW interactions, which in relatively large systems favor it with respect to a perpendicular layout, in which one molecule points with some C–H bonds toward the π system of the other. , The Δ E ZPE values with respect to the reactants will now be examined (Table ). For the complexes of systems 1, 2, 4, and 5, we start from the not unexpectedly rather close values of ca.…”
Section: Resultsmentioning
confidence: 99%
“…49 We have recently studied by quantum mechanical methods the growth of an aromatic system adsorbed on a model soot platelet, 55 and the feasibility of association of PAHs via vdW interaction. 56,57 In the latter study, it was concluded that, at high temperature, pure vdW stacking can hardly be a major factor in triggering soot nanoparticle inception. In fact, although energetic effects would suggest that larger interacting systems will be better stabilized, entropy changes work in the opposite direction.…”
Section: ' Introductionmentioning
confidence: 99%